2019
DOI: 10.1155/2019/2491291
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of MicroRNA-497 in Various Cancers: A Systematic Review and Meta-Analysis

Abstract: Background. Some studies showed that microRNA-497 (miR-497) might act as a prognostic biomarker of cancer. However, the conclusion was not consistent. The aim of this study was to investigate the prognostic role of miR-497 in various carcinomas. Methods. We systematically searched the databases of PubMed, Embase, Web of Science, Chinese National Knowledge Infrastructure (CNKI), and Wanfang Data to identify relevant studies. Two independent reviewers performed the data extraction and assessed the study quality.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…The downregulation of miR‐497 expression in PCa is consistent with its function in most tumours (Liu et al, 2019). Wang et al (2013) found that miR‐497 inhibited cell growth and induced apoptosis by activating caspase‐3 in PCa cells.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The downregulation of miR‐497 expression in PCa is consistent with its function in most tumours (Liu et al, 2019). Wang et al (2013) found that miR‐497 inhibited cell growth and induced apoptosis by activating caspase‐3 in PCa cells.…”
Section: Discussionsupporting
confidence: 53%
“…The sequence analysis of circ_SLC19A1 showed that it contained multiple binding sites for miR‐497. Studies have found that miR‐497 expression in many kinds of tumours is decreased, which can inhibit the occurrence and development of tumours (Liu et al, 2019). In addition, downstream target genes of miR‐497 were predicted, and septin 2 (SEPT2) was one the potential important target genes.…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, a meta-analysis of 12 studies (including a total of 989 cancer patients) revealed that tumor patients with a high level of miR-497 expression exhibited longer OS times ( 144 ). In 2019, a meta-analysis of 15 studies (including a total of 1,760 participants) revealed that lower miR-497 expression levels were significantly correlated with shorter OS time, but not disease-free survival or relapse-free survival, indicating that miR-497 was not significantly correlated with early prediction, but may be of value as a biomarker of long-term prognosis ( 145 ).…”
Section: Clinical Significance Of Mir-497mentioning
confidence: 99%
“…There have been reports of the prognosis of CRC based on immunohistochemistry staining to detect gene mutation or polymorphism [28, 29], or activation [30], which is only feasible after surgical procedures. One category of circulating biomarkers for CRC falls within the scope of gene regulation (microRNA or methylation) [31, 32]. Another category resides in serum metabolomics analysis [33].…”
Section: Discussionmentioning
confidence: 99%